PEMETAAN POLA INTRUSI AIR LAUT DI BEBERAPA DAERAH YANG MENJADI DESTINASI PARIWISATA DI KABUPATEN LOMBOK UTARA - Ni Putu Ety Lismaya Dewi; Indah Arry Pratama (SANGKAREANG, 2017)
North Lombok (KLU) is actively developing the tourism sector. One of the tourism sector with huge potential in KLU is the beach tourism. Various regions in KLU which became a tourist destination, local, national and international, among others Nipah beach, Malimbu, Pandanan, Gili Kodeq, Gili Indah, and Sire Beach. However, efforts to develop the tourism sector is experiencing various obstacles. One of the problems is a major constraint in the development of tourism sector in different regions KLU is the lack of existing facilities at tourist sites. Such facility including clean water, toilet facilities and security facilities. To that end, the provision of clean and adequate water into this matter urgently. The availability of clean water is often a visitor consideration in choosing a travel destination. The evaluation of the problem of seawater intrusion in coastal resorts North Lombok extremely important in efforts to manage groundwater resources, it is that the quantity and quality of groundwater supply in the long term to support tourism activities in KLU. The purpose of this study was to determine the patterns of freshwater availability vertically coastline as a result of salt water intrusion in some areas KLU tourism. In this research will be the process of digitization of the dots seawater intrusion in coastal resorts of North Lombok regency that will produce distribution maps of seawater intrusion in coastal resorts of North Lombok regency. The data obtained will then be analyzed descriptively and presented in the form of images, tables and graphs and discussed based on the need to address concerns and research purposes. Based on the analysis results can be seen that the highest level of salinity are in wells that were located closest to the shore while the lowest salinity values are in the wells were located 230 m from the beach. Wells salinity level citizens well residing in Malimbu Beach be in the range of 0.4% -1.233%. While the level of salinity of wells that were in Nipah Beach is in the range of 0% - 0.8%. Because salinity levels in the two sites are under 3%, then the water in the two sites are in the classification of freshwater. From this study it can be concluded that the availability of fresh water in Malimbu and Nipah are in good condition and able to support the needs of tourism in both locations.